Peran Kepolisian dalam Penegakan Hukum Tindak Pidana Pencabulan Anak di Padangsidimpuan - Srg, Bryan Ray; Trisna, Wessy; Marsella, Marsella (Universitas Medan Area, 2024)
The purpose of the research is to find out the role of the police in handling child molestation crimes, and to find out the obstacles in handling child molestation crimes. The research method used is normative juridical type research, which is research conducted to examine the application of legal provisions (positive law) related to the crime of child molestation. The data collection technique is library research and interviews with the Padangsidimpuan police, data analysis is with the same data analysis technique as qualitative analysis, namely, the data obtained is then systematically compiled for further qualitative analysis. From the results of the research that has been carried out, the author concludes that the role of the police in handling child abuse crimes The role of the police in handling child abuse crimes, carrying out coordination of the protection of women and children, coordination of social services, coordination correctional centers, and counseling. The obstacle in handling the crime of child molestation, the perpetrator fled, the perpetrator was unknown, and the victim did not want to speak.